Disclosures and Impacts of Impairment of Non-Current Assets in the Financial Statements: A Study on Listed Manufacturing Companies in Colombo Stock Exchange (CSE) in Sri Lanka - Logeswary, S.; Velnampy, T. (My University, 2013)
Nowadays many accounting standard setters want to move towards the relevance of fair value than reliability of historical value even accounting information has to maintain them in balance. The most percentage of value in financial statements is represented by non-current assets. And also the company act has insisted the implementing impairment test in the companies. Hence importance of impairment of assets has grown. The purpose of this study is to analyze the disclosures of impairment of non-current assets in applying LKAS 36 and their impact by inspecting the 5 years financial reports surveyed during the period from 2008-2012 of listed manufacturing companies in CSE. The disclosure of impairment was analyzed by using descriptive statistics and the impacts were evaluated by inferential statistics of regression and analyzed the relationship by correlation and coefficient between Impairment loss and selected accounting information of Return On Assets (ROA), Return On Capital Employed (ROCE), Net Profit Margin (NPM), Operating Profit Ratio (OPR) , and Earning Per Share( EPS). According to the findings 6% of reports disclosed very detailed information about the impairment. Nearly 90%of companies fail to give any reason to the impairment loss, even though they met the significant amount loss. All the companies have disclosed the accounting policies of impairment of assets. The results of analyzing impact of impairment show that, reported impairment losses had a significant impact upon reported profits. Loss making companies were more adversely affected by impairment losses than profitable companies. The sample company’s EPS dropped from 0.21 to -1.89 by recording Impairment loss. Hence the impairment loss was often a significant component of the reported overall loss. Future company financial reports on impairment could improve the disclosure to include a clear cause of impairment stated unambiguously in the annual reports with supporting value.
Keywords: Impairment of non-current assets; disclosure; impact